A chiral nickel DBFOX complex as a bifunctional catalyst for visible-light-promoted asymmetric photoredox reactions. Issue 20 (4th May 2018) - Shen, Xiang; Li, Yanjun; Wen, Zhaorui; Cao, Shi; Hou, Xinyi; Gong, Lei
Abstract : The enantioselective photoredox reaction of α, β-unsaturated carbonyl compounds and tertiary/secondary α-silylamines was enabled by a readily available single Ni II –DBFOX catalyst under visible light conditions. Abstract : The enantioselective photoredox reaction of α, β-unsaturated carbonyl compounds and tertiary/secondary α-silylamines was enabled by a readily available single Ni II –DBFOX catalyst (DBFOX = 4, 6-bis(( R )-4-phenyl-4, 5-dihydrooxazol-2-yl)dibenzo[ b, d ]furan) under visible light conditions. The non-precious chiral catalyst is involved in the photochemical process to initiate single electron transfer and at the same time provides a well-organized chiral environment for the subsequent radical transformations. Good to excellent enantioselectivities (80–99% ee) were obtained for the formation of chiral γ-amino carboxylic acid derivatives and γ-lactams.